Knowledge of Cervical Cancer among Females in North Central Nigeria - Gamde, Solomon M; Udo, Sekenimde; Ngozi, Chukwu M; Etim, Ibanga I; Biya, Abigail; Garba, Aminu; Abriba, Simon P (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Cervical cancer is a major cause of mortality among women of reproductive age group despite several measures initiated to halt the disease. Organized cytology-based screening is an effective technique in reducing the incidence and mortality of the disease. However, some women do not know what the screening is for. This study examined the knowledge on cervical cancer among women in North Central Nigeria. Method: This cross-sectional study was carried out on 242 females of age group 15 -55 years using an explorative structured questionnaire-base method from October - December 2023. Statistical Package for the Social Sciences (SPSS) version 26 was used for analysis. Results: The study found that 76.9% of the study population had never gone for cervical screening and the majority who are willing (60.2%) do not know when and where to get a screening test. The access to cervical cancer screening services is a major difficulty in the community. In addition, majority (93.8%) participants who held a higher education certificate or were currently pursuing an undergraduate degree, lack a clear understanding of the risk factors of cervical cancer and HPV vaccine. Conclusions: There is paucity of knowledge of the risk factors of cervical cancer among the study participants. To improve the knowledge, we advocated for awareness campaigns and affordable cervical cancer screening services. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 289-296